PHILOSOPHY OF ISLAMIC EDUCATION IN STUDY SOURCES AND OBJECTIVES OF HISTORY LEARNING AND ISLAMIC CULTURE - Suhari; Suhana Sarkawi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Learning Islamic history and culture is an important topic in Islamic education. Learning sources include books on Islamic history and culture, articles and previous research results, and film media. Learning objectives include increasing students' understanding of Islamic history and culture, increasing students' ability to appreciate and understand the diversity of Islamic culture, and increasing students' ability to develop attitudes of tolerance and respect for differences. Learning methods that can be used include scientific approaches, role playing methods, use of film media, and innovative learning methods assisted by learning media. Learning evaluation can be done using the Kahoot application or tests and quizzes. Teachers need to choose appropriate learning methods that suit students' needs, and carry out regular learning evaluations to determine the extent of students' understanding of the material being taught.